Rovibrational spectroscopy using a kinetic energy operator in Eckart frame and the multi-configuration time-dependent Hartree (MCTDH) approach - Sadri, Keyvan; Lauvergnat, David; Gatti, Fabien; Meyer, Hans-Dieter (The journal of chemical physics, 2014)
For computational rovibrational spectroscopy the choice of the frame is critical for an approximate separation of overall rotation from internal motions. To minimize the coupling between internal coordinates and rotation, Eckart proposed a condition [“Some studies concerning rotating axes and polyatomic molecules,” Phys. Rev. 47, 552-558 (1935)] and a frame that fulfills this condition is hence called an Eckart frame. A method is developed to introduce in a systematic way the Eckart frame for the expression of the kinetic energy operator (KEO) in the polyspherical approach. The computed energy levels of a water molecule are compared with those obtained using a KEO in the standard definition of the Body-fixed frame of the polyspherical approach. The KEO in the Eckart frame leads to a faster convergence especially for large J states and vibrationally excited states. To provide an example with more degrees of freedom, rotational states of the vibrational ground state of the trans nitrous acid (HONO) are also investigated.